Exploring the cognitive load of digital library information architecture in supporting e-learning at tertiary level of education/ Irni Eliana Khairuddin ... [et al.] - Khairuddin, Irni Eliana; Ahmad Uzir, Nora'ayu; Ahmad, Norzuraiza Rina; Khan, Mazlina Pati; Abdullah, Siti Nurul Maryam (Fakulti of Information Management, Universiti Teknologi MARA, 2015)
The digital revolution has brought vivid deviations to information access, retrieving and storage. The formation of digital libraries has made an essential influence on teaching and learning process. Moreover, an educational digital library may supply a fortune of educational resources which focusing at different target audience from primary school children to graduate student. Furthermore, the growth of the digital information has led to significant development in search engines. In line with that, information architecture (IA) is a current paradigm that has been progressively familiarized in most web development tasks today. IA is a process of organizing and managing information, where the usability plays an important role in the solutions created. On the other hand, cognitive load theory is concerned with the manner in which cognitive resources are focused and used during learning and problem solving. It is important to maintain the average cognitive load for each working memory task. This research is mainly to access the cognitive load for the current information architecture for digital library in supporting the e-learning process.